Learning environment for c programming language - Tee, Ji Ken (2017)
In this final year project, we will look into the adaptive e-learning approach that Moodle as a learning management system (LMS) can provide. Throughout the entire project, the student will focus on developing a C programming online module using the Moodle LMS. As C programming has been around for more than 30 years, it shows how matured and useful the language is in the computing world. It is, therefore, important that the young generation today can learn C programming in an effective way, in order to be well prepared for future contributions in the workplace. Equipped with technology in mind, we will apply the teaching of C programming into an LMS. The report starts with the introduction and background research on the Moodle system as well as a comparison with other similar LMSs. After that, there will be documentation on the steps taken for feature development on a freshly installed Moodle system. Each feature developed will undergo several testing methodologies. Also, the objectives of this project will be clearly highlighted in the first chapter. This ensures that every feature developed is in line with project objectives. Towards the end of the report, there will be discussions on concluding thoughts and future work that can be carried out.